2011
DOI: 10.1118/1.3652917
|View full text |Cite
|
Sign up to set email alerts
|

Flow characteristics in a canine aneurysm model: A comparison of 4D accelerated phase‐contrast MR measurements and computational fluid dynamics simulations

Abstract: Purpose: Our purpose was to compare quantitatively velocity fields in and around experimental canine aneurysms as measured using an accelerated 4D PC-MR angiography (MRA) method and calculated based on animal-specific CFD simulations. Methods: Two animals with a surgically created bifurcation aneurysm were imaged using an accelerated 4D PC-MRA method. Meshes were created based on the geometries obtained from the PC-MRA and simulations using "subject-specific" pulsatile velocity waveforms and geometries were th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 56 publications
0
34
0
Order By: Relevance
“…10-20 The hemodynamics (eg, the velocity distribution, inflow streamlines, and flow patterns) determined on 4D flow MR imaging have been validated by computational fluid dynamics studies in human cerebral aneurysms, 10,12,14 experimental canine aneurysms, 25 and life-size human aneurysm phantoms. 22,26,27 The feasibility of visualizing the aneurysmal inflow on 4D flow MR imaging has been confirmed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10-20 The hemodynamics (eg, the velocity distribution, inflow streamlines, and flow patterns) determined on 4D flow MR imaging have been validated by computational fluid dynamics studies in human cerebral aneurysms, 10,12,14 experimental canine aneurysms, 25 and life-size human aneurysm phantoms. 22,26,27 The feasibility of visualizing the aneurysmal inflow on 4D flow MR imaging has been confirmed.…”
Section: Discussionmentioning
confidence: 99%
“…4D flow MR imaging may yield poor-quality images due to motion artifacts attributable to a relatively long acquisition time 21 and limited spatial resolution. [9][10][11][12][13][14]17,20,22,[25][26][27] Because flow quantification by using 4D flow MR imaging requires at least 16 isotropic voxels over the vessel lumen area, 31 a spatial resolution of 1.0 mm in the isotropic voxel dimensions is needed to evaluate the flow conditions in aneurysms with a diameter of 4.0 mm. 22 Although only 1.5T MR imaging scanners are available at our institution, high-resolution MR imaging on greater than 3T instruments may make it possible to evaluate the inflow jets of aneurysms smaller than 4.0 mm.…”
Section: Discussionmentioning
confidence: 99%
“…18,19 Both 4D flow MR imaging and computational fluid dynamics studies, used to evaluate the hemodynamics of cerebral aneurysms, returned similar results with respect to velocity distributions, inflow streamlines, and intraaneurysmal flow patterns in human cerebral 19,21,23 and experimental canine aneurysms. 36 In addition, 4D flow MR imaging results were validated by computational fluid dynamics studies performed on a life-size human aneurysm phantom. [37][38][39] Moreover, previous studies confirmed the feasibility of depicting the aneurysmal inflow.…”
Section: Discussionmentioning
confidence: 99%
“…29 Another study compared 3D PC-MR imaging with CFD in canine aneurysm models. 30 All studies found a good qualitative agreement between both techniques and a moderate quantitative agreement. Note that the purpose of the CFD simulations in this study was to compare the results with the 3D PC-MR imaging measurements.…”
Section: Discussionmentioning
confidence: 99%